The hungry energised allergic disease-ridden matrix for financial decision dilemmas of entrepreneurs. (29th March 2022) - Sivasankaran, N.; Kanagaraj, A.; Israel, D.; Prasad, R.
Entrepreneurs face financial dilemmas on a regular basis. These dilemmas are centred on taking major financial decisions such as how much of cash, debt, fixed cost, working capital and dividend is good for the firm i.e. whether the entrepreneurs should increase or decrease the size of these financial decision variables in order to increase their profitability. The paper discusses in detail these five financial decision dilemmas and offers the decision guidelines/rules for the entrepreneurs using the HEAD matrix as an analytical tool.